Eco-friendly approach to thermal energy storage: Assessing the thermal and chemical properties of coconut biochar-enhanced phase change material - Rajamony R.K.; Paw J.K.S.; Pandey A.K.; Sofiah A.G.N.; Yadav A.; Tak Y.C.; Kiong T.S.; Mohanty A.; Soudagar M.E.M.; Fouad Y. (John Wiley and Sons Inc, 2025)
Phase change materials (PCMs) can absorb, store, and release substantial latent heat within a specific temperature range during phase transition and have gained huge attention due to environmental concerns and energy crises. However, PCMs have a significant downside in energy storage due to their relatively lower thermal conductivity, leading to inadequate heat transfer (HT) performance. The foremost aim of the research is to synthesize an eco-friendly coconut shell biochar (CSB) dispersed with organic A46 PCM in the temperature range of 44C to 46C to form a green nanocomposite. A two-step approach is adopted to formulate the nanocomposites with different weight concentrations (0.2% and 0.8%) of green CSB particles. The developed nanocomposite's thermal conductivity and chemical stability were examined using a thermal properties analyzer and a Fourier transforms infrared spectrometer. The developed biochar composites have excellent thermal conductivity (0.39 W/m K) compared with base PCM (0.22 W/m K). Also, the developed nanocomposites were physically mixed together; there were no additional functional groups formed compared to pristine PCM, and the prepared materials were composite. Furthermore, a numerical analysis was performed using two-dimensional energy modeling software to ascertain the HT rate of A46 composites. These thermally energized green nanocomposites show great promise for thermal energy storage and thermal management applications like battery thermal management, photovoltaic thermal systems, desalination systems, electronic cooling, building applications, and textiles. ? 2024 John Wiley & Sons Ltd.